Psychosocial stress in nursing work at a university hospital: effort-reward imbalance model (Research, Society and Development, 2022)
Objectives: to characterize psychosocial stress in nursing professionals at a university hospital using the Effort-Reward Imbalance model and to analyze the association of the resulting imbalance with the characteristics of the sample. Method: a cross-sectional study with 110 nursing workers from a university hospital located in the city of Rio de Janeiro who responded to the effort-reward imbalance scale and a sample characterization instrument in 2018. Bivariate analyzes were performed using Pearson's Chi-square test and Odds Ratio Estimation. Project approved by the research ethics committee. Results: effort was associated with family income and type of employment relationship, with age group and professional category showing a borderline association. The reward was not associated with any variable. Conclusion: the association of the effort subscale with family income and the type of employment relationship point to psychosocial stress, characterizing the imbalance due to the absence of reciprocity between effort and reward at work. There is a need for preventive measures by the organization in the face of psychosocial stress.